Analisis Peningkatan Kapasitas Produksi Menggunakan Alat Penggiling Kopi pada Usaha UD. Oikhoda (Jurnal Riset Manajemen dan Akuntansi, 2025)
Authentic Nias coffee production business UD. Oikhoda is a micro-enterprise whose coffee production has even been exported abroad. This Nias coffee production business has production activities where this production business focuses on producing aunthentic Nias coffee powder that is produced directly,and coffee beans originating from the region itself, namely Nias. UD. Oikhoda is still overwhelmed in meeting this market demand. As is known, the marketing of UD. Oikhoda’s coffee powder product has been considered to be exported abroad and several regions in Indonesia so that UD. Oikhoda should be able to meet this demand.from what researchers saw, this production business often does overtime in an effort to produce more ground coffee.In addition to promblems with the existing raw materials, it was revealed that frequent machine damage occurred, suspected to be from employees who lack mastery or skill in using the machine, resulting in less than optimal production activities. Researchers also that the lack of understanding and skills of empolyess in using the machine and the lack of maintenance carried out on these machines were among the factors causing machine damage.